Influência do antigo lixão do Roger, João Pessoa, nas águas subterrâneas locais - Fagundes, Giulliano de Souza (2010)
This study had the aim of evaluating the groundwater quality nearby the decommissioned Roger open dump in João Pessoa, Brazil, which was decommissioned in 2003 and occupies an area of 17 hectares, adjacent to the mangrove besides Sanhauá river, which increases the impact produced from the inadequate disposal of solid wastes. During the last three years of operation the open dump also received the solid wastes from the cities of Bayeux and Cabedelo. The monitoring of groundwater quality was done through six wells called P1, P2, P3, P4, P5 and P6, spread over the internal, direct influence and indirect influence areas of the decommissioned open dump. P1, P2, P3 and P4 were particular wells that the owner allowed to be included in the monitoring, while P5 and P6 were constructed in the internal area of the former open dump. Sampling occurred every three or four months during almost three years. The following parameters were monitored: pH, conductivity, hardness, color, turbidity, dissolved total solids, BOD, COD, oil and grease, chloride, ammonia, nitrite, nitrate, aluminum, plumb and thermotolerant coliform. For statistical treatment of collected data, analysis of variance through the GT-2 grafic method was employed. Results have shown that P5 and P6 presented the worst water quality indicators suggesting that the former open dump poses some influence on the local groundwater quality. However, oil and grease, thermotolerant coliform and chloride were found in all the wells, indicating that other sources of contamination are present in the site. The groundwater in the region of the decommissioned Roger open dump does not satisfy the standards for drinking water according to Brazilian legislation.